2017
DOI: 10.1097/yct.0000000000000426
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-term Cognitive Outcomes in Patients With Major Depression Treated With Electroconvulsive Therapy

Abstract: Objectives The risk of cognitive impairment is a concern for patients with major depressive disorder (MDD) receiving electroconvulsive therapy (ECT). Here, we evaluate the acute, short-term and long-term effects of ECT on tests of processing speed, executive function, memory, and attention. Methods Forty-four MDD patients receiving ECT (61% right unilateral (RUL), 39% mixed RUL-bitemporal, left UL and/or bitemporal lead placement underwent a cognitive battery prior to ECT (T1), after 2 sessions (T2), and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 51 publications
5
38
0
2
Order By: Relevance
“…Anterograde visual memory tested by the reproduction of a complex figure showed a different pattern to tests of verbal recall, with an improvement in scores from baseline to 4 months after ECT, and no evidence that it was influenced by the severity of depression. This is consistent with the improved scores found by most (Bodnar et al, 2016;Nuninga et al, 2018;Obbels et al, 2018), but not all (Vasavada et al, 2017), studies, of which none assessed the effect of mood state. The apparent improvement during follow-up is likely to be due to practice effects as discussed below.…”
Section: Psychological Medicinesupporting
confidence: 87%
See 1 more Smart Citation
“…Anterograde visual memory tested by the reproduction of a complex figure showed a different pattern to tests of verbal recall, with an improvement in scores from baseline to 4 months after ECT, and no evidence that it was influenced by the severity of depression. This is consistent with the improved scores found by most (Bodnar et al, 2016;Nuninga et al, 2018;Obbels et al, 2018), but not all (Vasavada et al, 2017), studies, of which none assessed the effect of mood state. The apparent improvement during follow-up is likely to be due to practice effects as discussed below.…”
Section: Psychological Medicinesupporting
confidence: 87%
“…While we have some confidence in baseline comparisons between patients and controls, for follow-up assessments, this applies only when patients performed significantly worse than controls (category verbal fluency and working memory). In particular, the improvement we found during follow-up on anterograde visual memory tested is likely to be due to practice effects as two studies have reported improved performance on a delayed complex figure task in healthy controls when repeated (Nuninga et al, 2018;Vasavada et al, 2017), although whether practice effects occur to the same extent in ECT-treated depressed patients is uncertain. While medication effects cannot be excluded as a cause of impairment, our results are broadly consistent with the deficits reported more generally in patients remitted from depression (Semkovska et al, 2019).…”
Section: Comparison Between Patients and Healthy Controlsmentioning
confidence: 90%
“…131 To the authors' knowledge, there are no studies specifically looking at cognitive side effects in catatonic patients, though it is worth noting that catatonia itself significantly impairs cognition, 27,150 and improvement on a brief cognitive measure, such as a clock drawing test, has been reported in catatonia responsive to ECT. 80,150,151 Studies looking at depression and other conditions have shown overall improvement of cognition with ECT, 152,153 suggesting that benefits of treatment outweigh the impact of side effects; this is likely true for catatonia as well. Risk for post-ECT delirium may be elevated in patients with catatonia compared to other indications for ECT; a study looking at associated factors found that presence of catatonia, longer seizure duration, high stimulus intensity, and bitemporal electrode placement increased risk, but that dexmedetomidine was preventive.…”
Section: Dovepressmentioning
confidence: 99%
“…ECT has been shown to be more effective on depressive symptoms than classic pharmacological treatment in unipolar ( The UK ECT Review Group, 2003 ) and bipolar depression ( Schoeyen et al, 2015 ), and is generally associated with lower rates of relapse in combination with pharmacotherapy in comparison with pharmacological intervention alone ( Elias et al, 2017 ; Jelovac et al, 2013 ). While concerns have been raised with respect to side-effects on cognitive functions, such as memory, these seem to be transient ( Kirov et al, 2016 ; Vasavada et al, 2017 ) and possibly related to the severity of the disorder ( Andrade et al, 2016 ). Overall, ECT is considered a safe therapeutic option for patients who do not respond to antidepressant medications and thus are at risk of experiencing prolonged periods of severe depression, leading to impaired quality of live and even life-threatening consequences, including suicidal acts and physical deterioration from lack of food and water intake.…”
Section: Introductionmentioning
confidence: 99%